Achieving a blue-excitable yellow-emitting Ca-LMOF phosphor via water induced phase transformation - Wu, Zhao-Feng; Tan, Bin; Fu, Zhi-Hua; Velasco, Ever; Liu, Xing-Wu; Teat, Simon J.; Zhu, Kun; Xing, Kai; Huang, Xiao-Ying; Li, Jing (Chemical science (Cambridge), 2022)
Luminescent metal–organic frameworks (LMOFs) with diverse structural features and promising fluorescence-based applications have attracted wide attention in the past two decades. In this work, a LMOF with the formula [Ca 4 (tcbpe-F) 2 (H 2 O) 3 ] (1, LMOF-411) has been constructed from calcium (Ca) and 1,1,2,2-tetrakis(4-(4-carboxyphenyl)phenyl)ethene (H 4 tcbpe-F). Compound 1 features a three-dimensional framework with a 10-nodal net topology. Due to the relatively high hydration energy of Ca 2+ , compound 1 readily transforms into a new phase formulated as [Ca(H 2 tcbpe-F)(H 2 O) 2 ] (1′) upon exposure to water. Combining experimental characterization and theoretical calculations, we elucidated the mechanism of H 2 O-induced phase transition from 1 to 1′. Notably, the water induced phase transformation can be detected visibly from the change in luminescence, which originates from the fluorescent linker. Compound 1 emits green light ( λ em = 490 nm) under UV excitation, while compound 1′ emits bright yellow light ( λ em = 550 nm) under blue excitation (450 nm). Compound 1′ represents the first Ca based LMOF yellow phosphor and its luminescence quantum yield reaches 68%. It can be coated directly onto a commercial blue light-emitting-diode (LED) chip to fabricate a white LED (WLED).